Ultrasound-Guided Fine Needle Aspiration Cytology of Supraclavicular Lymph Nodes in Suspected Lung Cancer: A Diagnostic Study - Devkota, Ganesh; Tripathi, Pratikshya; Gautam, Mahesh; Shrestha, Robinson (Medical Journal of Eastern Nepal, 2026)
BackgroundAccurate staging of lung cancer is essential for appropriate treatment planning. Supraclavicular lymph nodes are commonly involved in advanced disease and are easily accessible for sampling. Ultrasound-guided fine needle aspiration cytology (US-FNAC) provides a minimally invasive method for their evaluation. Objectives This study aims to evaluate the diagnostic performance of ultrasound-guided fine needle aspiration cytology (US-FNAC) of supraclavicular lymph nodes in patients with suspected lung cancer.MethodsThis prospective study included 40 patients with suspected lung cancer and detectable supraclavicular lymph nodes. US-FNAC was performed under ultrasound guidance. Cytological findings were compared with histopathology from lung biopsy in 27 patients. Diagnostic indices were calculated.ResultsAmong 40 patients, initial US-FNAC diagnosed 28 malignant, 5 suspicious, 6 benign/reactive, and 1 inadequate. Repeat FNAC of suspicious cases yielded 4 malignant and 1 benign; the inadequate case was excluded. Histopathology (n = 27) confirmed 24 malignant and 3 benign lesions. Final FNAC correctly identified all malignant cases, misclassifying 1 benign case. The diagnostic performance showed a sensitivity of 100%, specificity of 66.7%, positive predictive value of 96%, negative predictive value of 100%, and an overall accuracy of 96.3%.ConclusionsUS-FNAC is a highly sensitive and reliable technique for detecting metastatic lung cancer. Despite occasional false-positive findings, it remains a valuable tool for staging and guiding clinical management.